OPTIMIZING VIDEO AS INSTRUCTIONAL MEDIA IN GRAMMAR CLASS DURING COVID-19 PANDEMIC - Nurul Afidah (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2021)
ABSTRACT The aim of this study is to develop grammar instruction videos for students at grade VIII. This study uses Research and Development research design on its application, specializing in ADDIE model. Data collection were done using questionnaire to 10 eight grade students from Madinatul Ulum Junior High School and interview was done to gather data from the teacher. Through this study it is found that there is quite high demand on creating a creative and new teaching aid for teaching-learning process. Researcher developed video as instructional media that involved Simple Present Tense, Simple Past Tense, Present Continuous Tense, There is-There are, and Modals Can-Will-Must-Should as the topic disscused. Based on the data obtained on develop phase, 4.57 was from the material expert, 4.44 score was from the media expert and a score of 4.44 was obtained on the implementation process. The scores prove that the product were in good quality and worth to use. KEYWORDS: Instructional Media, Grammar, Video ABSTRAK Penelitian ini bertujuan untuk mengembangkan video pembelajaran pada materi grammar untuk siswa kelas VIII. Penelitian ini menggunakan jenis penelitian dan pengembangan yang mengadaptasi model ADDIE. Pada tahap analisa kebutuhan, peneliti menggunakan angket yang disebarkan kepada 10 siswa kelas VIII, serta wawancara kepada pihak guru untuk memperoleh data terkait media yang digunakan sebelumnya. Berdasarkan data tersebut, perlu dikembangkan sebuah media pembelajaran yang dapat membantu proses pembelajaran selama masa pandemi. Topik yang dibahas meliputi beberapa materi diantaranya: Simple Present Tense, Simple Past Tense, Present Continuous Tense, There is-There are, and Modals Can-Will-Must-Should. Berdasarkan data hasil validasi, diperoleh angka 4.57 untuk penilaian dari aspek materi serta 4.44 untuk penilaian dari aspek media. Dan saat tahap implementasi, diperoleh skor 4.44 yang bermakna media pembelajaran ini layak untuk digunakan. KEYWORDS: Media Pembelajaran, Grammar, Video